2012
DOI: 10.1109/jsen.2011.2179645
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Selectivity of Pt-Gate SiC Field Effect Gas Sensors by Dynamic Temperature Modulation

Abstract: Abstract-Based on a diode coupled silicon carbide field effect transistor with platinum as catalytic gate material, the influence of dynamic temperature modulation on the selectivity of GasFETs has been investigated. This operating mode, studied intensively for semiconductor gas sensors, has only recently been applied to field effect transistors. A suitable temperature cycle (T-cycle) for detection of typical exhaust gases (CO, NO, C 3 H 6 , H 2 , NH 3 ) was developed and combined with appropriate signal proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…The resulting signals, after pre-processing and feature extraction, were analyzed by linear discriminant analysis (LDA), a multivariate pattern recognition method which separates different classes of input data while trying to group data sets of the same assigned group (Klecka, 1980;Gutierrez-Osuna, 2002). The combination of TCO and LDA has shown to improve selectivity and sensitivity of gas sensors, both MOS sensors (Gramm et al, 2003;Meier et al, 2007;Reimann and Schütze, 2012;Leidinger et al, 2014) and other types, e.g., GasFET devices (Bur et al, 2012).…”
mentioning
confidence: 99%
“…The resulting signals, after pre-processing and feature extraction, were analyzed by linear discriminant analysis (LDA), a multivariate pattern recognition method which separates different classes of input data while trying to group data sets of the same assigned group (Klecka, 1980;Gutierrez-Osuna, 2002). The combination of TCO and LDA has shown to improve selectivity and sensitivity of gas sensors, both MOS sensors (Gramm et al, 2003;Meier et al, 2007;Reimann and Schütze, 2012;Leidinger et al, 2014) and other types, e.g., GasFET devices (Bur et al, 2012).…”
mentioning
confidence: 99%
“…The operating temperature of the sensor was modulated, i.e., run in temperature cycled operation, TCO, in order to increase the selectivity of the sensor [15], [24]. The chosen temperature cycle consists of three temperature plateaus, i.e.…”
Section: Sensor Setup and Operationmentioning
confidence: 99%
“…In temperature cycled operation pre-processing, in particular normalization of the data, is done on a cycle-bycycle basis. It was reported that setting the cycle mean to one is an effective method to reduce multiplicative drift [24]. However, it should be noted that when setting the mean of each cycle to one, information regarding discrimination of different gases which is contained in the raw data close to the mean of the cycle, is discarded.…”
Section: Pre-processing and Feature Extractionmentioning
confidence: 99%
See 2 more Smart Citations